CREM Is Correlated With Immune-Suppressive Microenvironment and Predicts Poor Prognosis in Gastric Adenocarcinoma - Yu, Kuai; Kuang, Linju; Fu, Tianmei; Zhang, Congkai; Zhou, Yuru; Zhu, Chao; Zhang, Qian; Zhang, Zhanglin; Le, Aiping (Frontiers in Cell and Developmental Biology, 2021)
The transcriptional repressor cAMP response element modulator (CREM) has important role in T cell development. In this study, we used the integrated Bioinformatics Method to explore the role of CREM in gastric cancer (GC). Our results showed high CREM expression was closely related with poorer overall survival in gastric cancer. By GSEA cluster analysis, we found that the high expression of CREM was associated with several cancer-associated pathway in GC. Moreover, single cell sequencing data showed that CREM is mainly localized in exhausted CD8+ T cell. Its prognostic value and the potential mechanism leading to T cell exhaustion in TME (Tumor Microenvironment). Similar results were obtained in glioma and non-small cell lung cancer. High expression of CREM, correlated with clinical relevance of GC, was associated with T cell exhaustion and M2-Polarization in gastric cancer. These findings suggest that CREM can be used as a prognostic biomarker in GC, Gliomas, LUAD. which might provide a novel direction to explore the pathogenesis of cancer.